The Shared Language - Alunni, Charles; Cortés, Tomas (Íkala, Revista de Lenguaje y Cultura, 1999)
Every language is the site of several potential analyses : the crossing of gender boundaries, the transfer of models or paradigms, and the situation of the interval between theoretical fields and grammatical models as extensions of the concept of "internal translation". These reflections encompass such problems as the political "translatability" of a doctrine or thought, translation policy, and the dandestine role of translators in the determination of cultural pDhcies.